Handbook of hydrocolloids - Phillips, Glyn O.; Williams, Peter A. (CRC Press ; Woodhead Pub., 2000)
The food industry is currently experiencing a rapid expansion in the demand for innovative food products and functional foods. These products rely heavily on hydrocolloids to provide specific textures, tastes, and behaviour during processing and cooking. The Handbook of hydrocolloids provides a reference to over twenty major hydrocolloids used in food processing. Each chapter examines all aspects of an individual hydrocolloid, including definition, methods of manufacture, commercial use, regulatory status, and technical data on optimising use to maximise process efficiency and end product quality.
Keywords: Hydrocolloids.; Food additives.; Colloids.; elektronické knihy; electronic books